Evaluating the geometric thinking levels of generation Z pre-service mathematics teachers in Indonesia - Naufal, Muhammad Ammar; Ihsan, Hisyam; Samsuddin, Auliaul Fitrah; Zainal, Zaid; Ashari, Nur Wahidin; Hassan, Muhammad Nasiru (Institute of Advanced Engineering and Science, 2025)
Geometric thinking abilities remain crucial in mathematics education, particularly for pre-service teachers who will shape future generations’ understanding of geometry. This study evaluates and compares the geometric thinking levels of generation Z pre-service mathematics teachers at Universitas Negeri Makassar (UNM) and Universitas Mulawarman (UNMUL) using the Van Hiele model. A quantitative comparative design was employed, involving 233 UNM and 227 UNMUL students selected through purposive sampling. The geometric thinking test (GTT) assessed students across five levels: visualization, analysis, informal deduction, formal deduction, and rigor. Results indicated that UNM students excelled in analysis and informal deduction, whereas UNMUL students displayed a broader distribution across all levels, with notable frequencies at visualization and formal deduction levels. A statistically significant difference in overall geometric thinking scores were identified, using the Mann-Whitney U test, with UNM students scoring higher. These findings emphasize the importance of adopting student-centered instructional strategies aligned with the Van Hiele model to enhance geometric thinking. Incorporating hands-on activities and technology is recommended to better prepare pre-service teachers for effective geometric instruction. The study provides insights for educators and policymakers to improve mathematics education by fostering higher geometric thinking levels in future teachers.